Construction of urban and non-urban spaces in travel magazine photographs - Šušmelj, Janja (Monitor ISH, 2007)
Photographs as cultural objects allow for numerous ways of interpretation within the social context of their use. In the case of travel discourse they offer many ways of reading the images according to how the social apparatus is involved in the construction of urban and non-urban spaces - that is, townscapes and images of nature in various locations throughout the world. The relationship between the viewer, the member of a society, and the world is mediated through these constructed images of spaces. Photographic discourse creates places of leisure representing the non-ordinary experience of places and reduces nature and cities to a few iconic images.
Keywords: prostor; urbani prostor; photography; fotografija; interpretacija; potovanje; discourse; diskurz